Comparative of Islam and West Learning Theory (A Study of the Learning Concepts of Imam al Ghazali and Jean Piaget) - Sepiyah Sepiyah (IAIN Ternate, 2021)
Discussion in this paper is about comparison Western and Islamic learning theory, in which the author tries to explore two ideas whose work is unquestionable, namely al Ghazali from Islamic thinkers and Jean Piaget from Western thinkers. This paper presents that the two thoughts are basically not much different, only the tendency of al Ghazali's thought which is influenced by Sufism makes his thinking in learning that it must be intended and aimed at the happiness of the hereafter. While Jean Piaget is more inclined to increase cognitive abilities, therefore Jean Piaget concludes, learning is basically an attempt to solve a problem. However, in this case the author does not tend to one party in the sense that the author tries to combine these differences to fill the respective vacancies from both parties. The method of this research is literature by trying to find a broad reference of course with an in-depth analysis, so as to produce the right conclusions.Keywords: Learning, al Ghazali, Jean Piaget and learning theory